Concepto y Representación de la Violencia de Género: Reflexiones sobre el Impacto en la Población Joven (Concept and Representation of Gender-based Violence: Reflections about the Impact on Young People) - Belén Zurbano Berenguer; Irene Liberia Vayá; Beatriz Campos Mansilla (Oñati Socio-Legal Series)
Recent studies and reports reveal that young people have a distorted concept of gender-based violence and their tolerance towards it does not decrease. There is a context of institutional concern about prevention and eradication of gender-based violence in Spain. In this context, this paper reflects on gender-based violence in order to compare the collective adolescent-young imaginary and social messages sent by the media on this problem.